Recovery and long-term health outcomes of SARS-CoV-2 infection in a prospective cohort in an urban setting, Kenya - Isaac Kisiangani; Ângela Jornada Ben; Elke Wynberg; Welcome Wami; Samuel Iddi; Idah Kinya; Anna Vassall; Catherine Kyobutungi; Abdhalah Ziraba; John Njeru; Olive Mugenda; Marion Wangui Kiguoya; et al. (Global Health Action)
Background Evidence on long COVID remains limited in sub-Saharan countries. Objective This study explored the occurrence of COVID-19-related symptoms and factors affecting recovery and long COVID severity in Nairobi, Kenya. Methods A prospective cohort of individuals testing positive for SARS-CoV-2 between February 2022 and February 2023 was followed until June 2023. COVID-19-related symptoms were assessed every three months. Time to recovery was analyzed using survival analysis, while factors affecting recovery factors and long COVID severity using Cox proportional hazard and Poisson regression, respectively. Results Among 291 participants (median age 34, 59.1% female), 42 (14%) had severe/critical infection. At 6 and 12 months post-positive PCR, 53.1% and 33.5% had ≥ 1 COVID-19-related symptoms, respectively. Fatigue (40.2%), pain (36.8%), sore throat (36.8%), headaches (36.4%), and loss of strength (31.6%) were most common. Median time to recovery was longer for severe/critical cases than mild/moderate (234 vs 206 days, p = 0.016). Participants aged 40–64 years experienced slower recovery than those aged < 40 years (aHR = 0.635 [95%CI, 0.429;0.941]). Participants with tertiary education recovered faster than those with primary education (aHR = 1.869 [95%CI, 1.050;3.327]). Long COVID severity was associated with female sex (aIRR = 1.418 [95%CI; 1.078;1.864]), tertiary education (aIRR, 0.489 [95%CI, 0.415;0.576]), and ≥ 1 comorbidity (aIRR = 2.415 [95%CI, 1.639;3.559]). Conclusions Six months post-infection, half had lingering symptoms, with a third still affected after a year. Recovery was faster in younger, educated individuals, while severe long COVID was more common in women, those with low education and pre-existing conditions. The burden of long COVID in Kenya requires support for vulnerable groups.